BROLUCIZUMAB FOR WET-AGED RELATED MACULAR DEGENERATION PATIENTS : TOO GOOD TO BE TRUE - Purbonegoro, Tania; Prayogo, M. Eko; Agni, A. Nurini; W., Tri Wahyu; Supanji, Supanji; S.W., Firman; Sasongko, M. Bayu (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2023)
Introduction & Objective: Brolucizumab is the newest anti-vascular endothelial growth factor (anti-VEGF) drug. It showed superior anatomic outcomes compared to other anti-VEGF and noniferiority best corrected visual acuity (BCVA) results for Wet-Aged Related Macular Degeneration (Wet-AMD) patients. In Yogyakarta, its been only used in few patients and we want to report the Effectiveness and safety of brolucizumab in Wet-AMD patients in Yogyakarta. Method: In this retrospective study, all neovascular AMD (nAMD) Patients who underwent brolucizumab intravitreal injections between December 2021 and January 2023 at YAP Eye Hospital were studied. Patient’s demographic data, before and after intravitreal brolucizumab injections (central subfield thickness, intraocular pressure and BCVA) were assessed. Result :This study included 6 eyes of 6 patients ( 3 women) with a mean age of 69.5 years old. The mean follow- up period was 27 ± 10.1 weeks after the first injection of brolucizumab. Three patients were naïve nAMD patient, never got any intravitreal injections and three anti-VEGF experienced nAMD patients with ranibizumab or aflibercept injections prior to brolucizumab. Mean BCVA at baseline (before brolucizumab injection) was 0.12 decimal (6/48) and was 0.29 decimal (6/20) at the last follow-up. Five out of six patients visual acuity were improved,one patient had constant bcva. Four out of six patient central subfield thickness were reduced, none of the patient intraocular pressure increased over 21 mmhg. None of the patient reported any signs of inflammation, vasculitis, or any other ocular or systemic adverse effects. Conclusion :This limited data demonstrated that brolucizumab was safe and effective in stabilizing BCVA for both of nAMD patients who had undergone previous treatment with other anti-VEGFs agents and naive. Future larger multicenter collaborative studies are warranted.